2018
DOI: 10.29121/granthaalayah.v6.i1.2018.1601
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Plant Growth Promoting Rhizobacteria (Pgpr) in Disease Control Important in Plants Onion (Allium Ascalonicum L.)

Abstract: Red onion (Allium ascalonicum L.) is one of many horticultural crops consumed by humans as a mixture of spices. For household consumption of about 635 700 tonnes, non-household consumption such as the manufacturing industry amounted to 719 200 tonnes, the sum total of 1.35 million meaning that the deficit for the onion. The purpose of this study was to gain insight about PGPR in increasing the growth and yield of onion, PGPR role in controlling the disease in onions, PGPR concentration in controlling the disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Use plants with IAAproducing bacteria to increase growth and yield. A similar result has been cited by (Fernandes et al, 2018 andSutariati et al, 2019). In addition to, Spirulina extract amino acids (methionine, glycine, tryptophan and phenylalanine) increase the growth substances and enhance number of leaves and leaf area/plant (Yassen et al, 2018 andNoroozlo et al, 2019).…”
Section: Resultssupporting
confidence: 87%
“…Use plants with IAAproducing bacteria to increase growth and yield. A similar result has been cited by (Fernandes et al, 2018 andSutariati et al, 2019). In addition to, Spirulina extract amino acids (methionine, glycine, tryptophan and phenylalanine) increase the growth substances and enhance number of leaves and leaf area/plant (Yassen et al, 2018 andNoroozlo et al, 2019).…”
Section: Resultssupporting
confidence: 87%
“…Bacterial growth promoting bacteria on red onion plants had been isolated and characterized, including nitrogen fixation, phosphate solubilization, and IAA synthesis [16,17]. Selected strains were also able to increase vigor and viability of purple onion seeds [16], increase plant height, number of leaves, number of bulbs, fresh and dry weight of bulbs [18], increase growth rate and tolerance index [19]. Besides, for the antagonistic ability of PGPR, the study of Fernandes et al (2018) had shown the ability to control wilt disease caused by Fusarium on red onions [18].…”
Section: Introductionmentioning
confidence: 99%
“…Selected strains were also able to increase vigor and viability of purple onion seeds [16], increase plant height, number of leaves, number of bulbs, fresh and dry weight of bulbs [18], increase growth rate and tolerance index [19]. Besides, for the antagonistic ability of PGPR, the study of Fernandes et al (2018) had shown the ability to control wilt disease caused by Fusarium on red onions [18]. Fusarium is the largest genus of fungi causing wilt disease for many crops.…”
Section: Introductionmentioning
confidence: 99%
“…This condition is possible because some bacteria can enter the inside of the plant roots, associated with plants, and also fix nitrogen, so plant nutrients are well maintained. Bacteria colonize tissues in plants so that it stimulates plants to increase the production of secondary metabolites that play a role in plant resistance, including the production of indole acetic acid (IAA) hormone, increased activity of fungal cell wall-degrading enzymes (peroxidase, chitinase, ß-1.3 glucanases), pathogenesis-related protein (PR), and phytoalexin [8,9].…”
Section: Introductionmentioning
confidence: 99%